Lung adenocarcinoma with mixed solid and crazy‐paving appearances. Issue 10 (4th October 2021) - Abdul Kadir, Roqiah Fatmawati; Hanafiah, Mohammad; Johari, Bushra; Zainudin, Lily Diana
Abstract: "Crazy paving" on CT images refers to the superimposition of ground‐glass opacity and linear pattern resembling irregularly shaped paving stones. Initially, "crazy paving" was described as a pathognomonic sign of alveolar proteinosis. Subsequently, this pattern has been reported in a variety of disorders of the lung. We demonstrated CT images of lung adenocarcinoma demonstrating both solid and crazy‐paving appearances. Abstract : "Crazy paving" on CT images refers to the superimposition of ground‐glass opacity and linear pattern resembling irregularly shaped paving stones. Initially, "crazy paving" was described as a pathognomonic sign of alveolar proteinosis. Subsequently, this pattern has been reported in a variety of disorders of the lung. We demonstrated CT images of lung adenocarcinoma demonstrating both solid and crazy‐paving appearances.